Industry and territorial structure of small and medium entrepreneurship and its socio-economic role in modern economy - S. V. Kuregyan; Yu. V. Meleshko; K. V. Skoraya (Вестник Северо-Кавказского федерального университета)
Introduction. The state and development of small and medium businesses is an important component of socioeconomic security of the state, ensuring diversification of the economy, filling the consumer market with a variety of goods and services, ensuring employment and, accordingly, social and economic security. In conditions of global technological uncertainty, it becomes important to update the theoretical and methodological foundations for the development of small and medium-sized businesses as one of the basic links of the national economy. Goal. The article is devoted to the study of the sectoral and territorial structure of small and medium-sized businesses. Materials and methods. The theoretical basis of the research is the results of scientific and practice-oriented works in the field of small and medium-sized enterprises; the works of domestic and foreign scientists devoted to the description of the factors determining the state and development of small and medium-sized enterprises. Results and discussion. The article is devoted to the study of sectoral and territorial structure of small and medium-sized businesses. Small and medium-sized businesses in rural settlements in the Republic of Belarus are still poorly diversified by types of economic activity, which means that there is a real opportunity to increase their role in ensuring high rates of socio-economic development of small and medium settlements. Conclusion. It was found that the socio-economic role of small and medium businesses in modern economy lies, first of all, in significantly increasing the adaptive capabilities of the national economy to changes (including shocks) in global and domestic markets. They are also expected to help increase the level and the quality of life of the population of individual regions and the entire country.